Life cycle assessment of ammonia utilization in city transportation and power generation - Bicer, Yusuf; Dincer, Ibrahim (ELSEVIER SCI LTD, 2018)
The main reason of climate change is particularly attributed to transportation and power generation in the world. Therefore, clean fuels alternatively emerge as potential solutions rather than carbon intensive hydrocarbons. In this study, carbon-free fuel ammonia is proposed to be utilized in the city transportation and power generation to reduce the environmental impacts of conventional fuels. Ammonia is electrochemically produced where required hydrogen is supplied from the wind-driven water electrolysis. The processes are analyzed from raw material extraction to vehicle disposal using life cycle assessment methodology. The results imply that greenhouse gas emissions from an ammonia driven vehicle are in the range of 100 g carbon dioxide eq. per km that is considerably lower than gasoline (270 g) and diesel (230 g) driven vehicles. Furthermore, using ammonia in the power plants can significantly reduce the total global warming potential corresponding to about 60% of natural gas-fired power plant. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Energy; Life cycle assessment; Ammonia; Power production; Transportation; Clean fuel; ELECTROCHEMICAL SYNTHESIS; ATMOSPHERIC-PRESSURE; IGNITION ENGINE; NATURAL-GAS; HYDROGEN; FUEL; VEHICLES; DIESEL; CELL; TECHNOLOGIES; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology